From screens to cognition: A scoping review of the impact of screen time on cognitive function in midlife and older adults - Rinanda Shaleha; Nelson Roque (Digital Health)
Background With increasing digital engagement across the lifespan, understanding how screen use influences cognitive aging is a growing public health priority. While much research has focused on younger populations, the cognitive implications of screen time in midlife and older adulthood remain underexplored. This scoping review synthesizes recent evidence on the associations between screen-based behaviors and cognitive outcomes in adults aged 40 and older. Methods Following PRISMA-ScR guidelines, we systematically searched PubMed and CINAHL for studies published between 2018 and 2023. Eligible studies examined the relationship between screen use and cognitive function in adults aged 40 and above. Data were charted across screen types, cognitive domains, and study characteristics. Results Seventeen studies met the inclusion criteria. Active screen use was generally associated with better cognitive outcomes, particularly in memory, executive function, and attention. In contrast, passive screen use was linked to poorer outcomes, including verbal memory and global cognition declines. Findings varied across cognitive domains and were influenced by moderators such as education, physical activity, sleep quality, and digital attitudes. Conclusions Screen time during midlife and older adulthood carries both risks and potential cognitive benefits. Its effects are specific to different domains and depend on context. Future research should adopt more nuanced, longitudinal, and inclusive approaches to guide digital health strategies that promote cognitive well-being in aging populations.